Analisis Komparatif Penerima Layanan Hukum Pro bono dengan Layanan Hukum Berbayar di Indonesia - Sindy Tjotjomare; I Putu Edi Rusmana; Dewa Krisna Prasada; Dewa Ayu Putri Sukadana (Cattleya Darmaya Fortuna, 2026)
This study aims to conduct a comparative analysis between recipients of pro bono legal services and paid legal services in Indonesia, focusing on their effectiveness, quality of legal assistance, and practical challenges, particularly in the Bali region. The research employs an empirical juridical method, which examines how law operates in practice (law in action). Primary legal materials include Law Number 16 of 2011 on Legal Aid, Supreme Court Regulation Number 1 of 2014 on Guidelines for Providing Legal Services for the Poor in Court, and the Indonesian Advocates’ Code of Ethics, while secondary materials consist of legal literature and previous research. The findings reveal that the implementation of pro bono legal services has not been fully effective despite having a solid legal foundation. Major challenges include delayed disbursement of government funds, limited budget allocation, and insufficient facilities and human resources within legal aid institutions. These factors negatively affect the motivation, professionalism, and effectiveness of advocates in providing legal assistance to underprivileged communities. Conversely, paid legal services tend to operate more efficiently due to clear contractual relationships between lawyers and clients, supported by sufficient financial resources, resulting in higher service quality and client satisfaction. In conclusion, the disparity in effectiveness between pro bono and paid legal services is not solely driven by economic factors but also by the suboptimal implementation, funding mechanisms, and oversight of legal aid policies in Indonesia.